El dibujo infantil para identificar la personalidad de las niñas y niños de 4 a 5 años de edad de la escuela de educación general básica Dra. Matilde Hidalgo de Procel N°1 de la ciudad de Loja. Periodo 2014- 2015 - Cartuche Jaramillo, Jessica Daniela (2016)
The present investigation began with a study about infantil draws to identificate children´s personality between 4 and 5 years old of General Basic Dra. Matilde Hidalgo de Procel N° 1 school in Loja. School year 2014-2015. The overall objective is to help to identify the personality througer the infantil draw for children´s between 4 and 5 years old. For do this, we have used the following methods: scientific, analytical, synthetic, hermeneutical and statistical. The technique used is the rubric made from family´s test, and the instrument used is family´s test applied to a population of 42 children. The developing of the camp´s investigation begin with the recollection of the recollection information through a rubric of family´s test that was applied to the children, which has been obtained the following results: 30 children representing 71% present born leader personality, security in themselves, positive and an easy interpersonal relationship. In conclusion, infantil draw is important as a means of identification of the personality, since the child expresses emotions, feelings and moods, almost without realizing it.